From open government to open parties in Europe. A framework for analysis - Villaplana, F. Ramón; Megías, Adrián; Sandri, Giulia (Frontiers in Political Science, 2023)
Open government (OG) is an increasingly used management model among the public administrations of European countries and of the European Union, which is currently working on The Path to the Digital Decade. This supposes the application of measures to promote proximity and citizenship's prominence in many public policies, leading to improved quality of democracy. Furthermore, the COVID-19 pandemic has contributed to a forced digitalization of many public services. Despite the fact that studies on OG do not usually focus on them, political parties are essential actors for the success or failure of OG measures, both from a bottom-up and a top-down perspective, on public administration transformation. Moreover, political parties are transforming themselves into more open organizations at the same time. We define open parties as political parties with high standards in transparency, participation, and collaboration. They also feature high degrees of organizational digitalization. This article proposes a framework for analyzing political parties' openness and explores available empirical data on different aspects related to OG in the European context. We have found that most parties possess a good level of local organizational strength but still need to reach better levels of anticorruption commitment, to form stronger ties with affiliated organizations, and especially to improve the participation of members and activists in their decision-making. Furthermore, elitism, clientelism, and populistic rhetoric represent significant obstacles that could hinder the party reform process.